Implicating Ultrasonication and Heat–Moisture Treatments as a Green and Eco-Friendly Approach for Dual Physical Modification of Eleocharis tuberosa Starch to Improve Its Physico-Chemical and Functional Properties - Zafarullah Muhammad; Rabia Ramzan; Chen Ana; Muhammad Afzaal; Adnan Abbas; Muhammad Safiullah Virk; Abdullah; Wu Sun; Guoqiang Zhang (Foods)
Dual-physical modification is an eco-friendly and waste-free approach for enhancing the functionality of native starches compared with a single modification. In the present study, the individual and combined interrelating effects of hydrothermal (heat moisture (HM) with 15%, 20%, and 25% moisture) and non-thermal (ultrasonication (US) with 200, 400, and 600 power (W)) on the physical modification of Eleocharis tuberosa (Chinese water chestnut (CWCS)) starch were studied. Furthermore, their effects on the morphology, FTIR, XRD, crystallinity, thermal, pasting, swelling power, solubility, rheological characteristics, and in vitro digestibility of native and modified starches were investigated. The results indicated a consistent B-type structure of CWCS, with a significant decrease in the crystallinity (22.32 ± 0.04–28.76 ± 0.02%), which was linked with ΔH (19.65 ± 0.01–12.18 ± 0.06 Jg−1) and amylose content (34.67 ± 0.07–40.73 ± 0.11%). The absorbance ratio 1048/1025 specified that the combination of HM-US compacted the short-range order degree up to 1.30 for HM25–US600-CWCS. The starch treated with HM, followed by the US, considerably amplified the setback, peak, and final viscosities compared with the HM-treated starch. The rheological analysis demonstrated that the fluidity of CWCS was enhanced (G′ > G″, tan δ < 1) by the synergistic effect of HM and US, increasing the resistivity toward deformation during paste development. The dual-modified starch exhibited a slower glucose release rate with increasing moisture (25%) during HM and 600 W during the US, with higher RS contents of 45.83 ± 0.28% and 43.09 ± 0.12%, respectively. Dual-physical modification exhibited a significant aptitude for modifying native starches structurally and functionally as a substitute for product formulation with a low glycemic index.